SATISFACTION EVALUATION OF USING E-LEARNING MEDIAIN FACULTYOF PUBLIC HEALTH UNIVERSITY MUHAMMADIYAH ACEH - Akbar Akbar; Nugroho Nugroho; Lazuardi Lazuardi (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
Information technology can not be denied that it has proved to be very large in the advancement and improvement of the quality of education in this country. Development towards e-learning education is a must for the quality standards of education can be improved because e-learning is a use of digital technology that can deliver a wide range of information in learning. The availability of hardware, software and other supporting facilities such as the internet network at the Faculty of Public Health University Muhammadiyah Aceh can be used as much as possible so that the transformation of education from the conventional learning system into a digital learning system by using e-learning is based on information technology.The design of this study was quantitative and qualitative research with action research approach. The subjects in this study purposive sampling determined by the number of 33 people consisting of elements of the leadership, faculty, and students. Instrument research include guidelines for in-depth interviews, observation guides, brainstorming guides, questionnaires, field notes and other devices in accordance with the development course of study. Has developed a digital learning system using the Dokeos. From the aspect of technology has been supported for the hardware and software. Overall the respondents have used e-learning system and no major obstacles. The results of the evaluation of the degree of ease of reaching the average value of 4.25 with a range from 4.18 to 4.36, the willingness of the average utilization reached a value of 3.89 with a range from 2.29 to 4.75 and also the willingness to support an average of value of 4.83 with a range between 4.39 to 5.0. Thus, it can be seen that the whole has a value above the median number = 3, which means the respondents felt a satisfaction which is felt by the high compliance is expected.Keywords: E-Learning, Dokeos Platform, Information Technology, Education